2022
DOI: 10.1186/s12913-022-07737-5
|View full text |Cite
|
Sign up to set email alerts
|

Competent and deficient provision of childbirth services: a descriptive observational study assessing the quality of intrapartum care in two provinces of the Democratic Republic of the Congo

Abstract: Background A majority of women in the Democratic Republic of the Congo (DRC) give birth in a health facility, but maternal and newborn mortality remains high. In rural areas, the quality of facility-based delivery care is often low. This study examines clinical quality of intrapartum care in two provinces of the DRC. Methods We observed process and input elements of delivery care provision at 29 facilities in Kwilu and Kwango provinces. Distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…High-quality intrapartum care is critical to the survival of the mother and the newborn [25]. However, the lack of essential equipment in this study was reported to be a potential impediment to the provision of quality care for pregnant women in the labour units of the selected hospitals.…”
Section: Equipment Availability Effectiveness and Maintenance During ...mentioning
confidence: 76%
“…High-quality intrapartum care is critical to the survival of the mother and the newborn [25]. However, the lack of essential equipment in this study was reported to be a potential impediment to the provision of quality care for pregnant women in the labour units of the selected hospitals.…”
Section: Equipment Availability Effectiveness and Maintenance During ...mentioning
confidence: 76%
“…The management of the health system and maintenance of supply chains is further challenged by the country's geographical features, the absence of road networks in many areas, and a long history of conflicts. Despite these challenges, the country has achieved reductions in maternal and child mortality over the past two decades and has managed to improve coverage of essential health services, although the quality of health services remains low (World Development Indicators, INS 2019;Clarke-Deelder et al 2019;Perales et al 2020;Fink, Kandpal, and Shapira 2022;Brenner et al 2022).…”
Section: Background Health System and Family Planning In Drcmentioning
confidence: 99%